The River Runs Black : The Environmental Challenge to China's Future - Economy, Elizabeth, 1962- (Book collections on Project MUSE., 2010)
Examines the environmental problems developing in China due to rapid economic growth during the past quarter-century, and looks at current and future implications of these issues.